2018
DOI: 10.1002/lom3.10237
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of marine zooplankton community structure through environmental DNA metabarcoding

Abstract: Zooplankton dominate the abundance and biomass of multicellular animals in pelagic marine environments; however, traditional methods to characterize zooplankton communities are invasive and laborious. This study compares zooplankton taxonomic composition revealed through metabarcoding of the cytochrome oxidase I (COI) and 18S rRNA genes to traditional morphological identification by microscopy. Triplicates of three different sample types were collected from three coral reef sites in the Florida Keys National M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
96
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(114 citation statements)
references
References 55 publications
11
96
0
Order By: Relevance
“…The sum of the detections for each genus (i.e., presence/absence) has been combined for all primer sets variable seabed characteristics, which play an important role in distribution of megafauna as they impact several factors, including larval settlement, anchorages, and shelter (Kedra, Renaud, Andrade, Goszczko, & Ambrose, 2013;Preez, Curtis, & Clarke, 2016). Our observations of distinct patterns of community structure depicted using either COI and 18S primer sets are consistent with several studies that have shown an effect of markers on the detection rate of marine invertebrates (Djurhuus et al, 2018;Drummond et al, 2015;Elbrecht et al, 2017;Kelly et al, 2017;Shaw et al, 2016). Variation in eDNA community structure was intermediate between the variation observed using the two different species collection approaches.…”
Section: Overall Biodiversity and Community Structuresupporting
confidence: 90%
“…The sum of the detections for each genus (i.e., presence/absence) has been combined for all primer sets variable seabed characteristics, which play an important role in distribution of megafauna as they impact several factors, including larval settlement, anchorages, and shelter (Kedra, Renaud, Andrade, Goszczko, & Ambrose, 2013;Preez, Curtis, & Clarke, 2016). Our observations of distinct patterns of community structure depicted using either COI and 18S primer sets are consistent with several studies that have shown an effect of markers on the detection rate of marine invertebrates (Djurhuus et al, 2018;Drummond et al, 2015;Elbrecht et al, 2017;Kelly et al, 2017;Shaw et al, 2016). Variation in eDNA community structure was intermediate between the variation observed using the two different species collection approaches.…”
Section: Overall Biodiversity and Community Structuresupporting
confidence: 90%
“…These facts emphasize that although eDNA has the potential of providing an enormous amount of information about an ecosystem, traditional surveys have distinct value and should continue in conjunction with eDNA surveys for more robust and accurate assessments of biodiversity (Djurhuus et al, ; Kelly et al, ). In fact, visual surveys can detect species missed by eDNA, which is something to keep in mind when using eDNA as a biodiversity monitoring tool (Djurhuus et al, ; Kelly et al, ). This discrepancy can be partly due to primer bias and the limitations of the number of distinct species a primer can recover (Parada, Needham, & Fuhrman, ; Stat et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, visual surveys can detect species missed by eDNA, which is something to keep in mind when using eDNA as a biodiversity monitoring tool (Djurhuus et al, 2018;Kelly et al, 2017). This discrepancy can be partly due to primer bias and the limitations of the number of distinct species a primer can recover (Parada, Needham, & Fuhrman, 2016;Stat et al, 2017).…”
Section: Limitations and Advantages Of Ednamentioning
confidence: 99%
See 1 more Smart Citation
“…DNA-based methods are revolutionizing the analysis of biodiversity, as they offer advantages over traditional, visual, and morphological survey methods (Thomsen &Willerslev, 2015). Accordingly, eDNA metabarcoding approaches have been successfully employed to characterize specific marine plankton communities in natural seawater samples, such as zooplankton, mesozooplankton, and full eukaryotic plankton diversity (Chain, Brown, MacIsaac, & Cristescu, 2016;Deagle, Clarke, Kitchener, Polanowski, & Davidson, 2017;de Vargas et al, 2015;Djurhuus et al, 2018;López-escardó et al, 2018;Villarino et al, 2018), as well as benthic communities from both soft (Guardiola et al, 2015;Lejzerowicz et al, 2015;Pawlowski, Esling, Lejzerowicz, Cedhagen, & Wilding, 2014) and hard (Leray & Knowlton, 2015;Wangensteen, Cebrian, Palacín, & Turon, 2018;Wangensteen, Palacín, Guardiola, & Turon, 2018) bottom habitats.…”
mentioning
confidence: 99%